The construction waste management framework for reducing illegal dumping activities in the construction industry - Abd Rahim, Mohd Hilmi Izwan (2019)
Nowadays, an increasing number of construction projects in Malaysia have contributed to the production of construction waste. Additionally, the production of construction waste from construction projects has had a negative impact on the environment, especially through illegal dumping activities. To date, comprehensive criteria for construction waste management in developing countries have not been clearly defined. Therefore, further research needs to be done on construction waste management in Malaysia. The main objective of this research is to develop the construction waste management framework for reducing illegal dumping activities. Semi-structured interviews were conducted with 25 stakeholders from government, private sector, construction players and cleaning contractor. Furthermore, data’s from the semi-structured interviews were analysed via content analysis using NVivo 10. The interviews finding were been transcribe to the Microsoft Word and analyse using Nvivo Software to figure out the significant theme and sub theme related to research objectives. Significant findings were used as potential improvements in the research to reduce illegal dumping activities. Hence, finding from this research has highlighted that currently there are lack implementation of proper construction waste management. Additionally, new findings found that awareness, enforcement, guidelines, cost, training and development, and technology are the most significant elements can be implemented in propose framework. The elements in the framework were divided into actions which need to be undertaken by construction players and those which require government enforcement. Finally, the proposed framework was evaluated by experts from the construction industry to obtain feedback. In conclusion, proposed framework will help stakeholders to identify strategies to reduce illegal dumping activities, increase awareness and seek better solutions for construction waste management in the construction industry.